Age-Dependent Changes of Thinking about Verbs - Bonivento, Carolina; Tomasino, Barbara; Garzitto, Marco; Piccin, Sara; Fabbro, Franco; Brambilla, Paolo (Frontiers in Behavioral Neuroscience, 2017)
We investigated the knowledge of emotional and motor verbs in children and adolescents from three age ranges (8-11, 12-15, 16-19 years). Participants estimated the verbs familiarity, age of acquisition, valence, arousal, imageability and motor- and emotion-relatedness. Participants were familiar with the verbs in our dataset. The younger (8-11) attributed an emotional character to the verbs less frequently than the middle (12-15) and the older (16-19) groups. In the 8-11 group males rated the verbs as emotion-related less frequently than females. Results indicate that processing verbal concepts as emotion-related develops gradually, and after 12-15 is rather stable. The age of acquisition (AoA) develops late: the older (16-19) had a higher awareness in reporting that they learnt the verbs earlier as compared to the estimations made by the younger (8-11 and 12-15). AoA positively correlated with attribution of emotion relatedness meaning that emotion-related verbs were learned later. Arousal was comparable across ages. Also it increased when attributing motor relatedness to verbs and decreased when attributing emotion relatedness. Reporting the verbs’ affective valence (happy vs unhappy) changes with age: younger (8-11) judged the verbs generally more ‘happy’ than both the older groups. Instead the middle and the older group did not show differences. Happiness increased when processing the verbs as motor related and decreased when processing the verbs as emotion related. Age affected imageability: the younger (8-11) considered the verbs easier to be imagined than the two older groups, suggesting that at this age vividness estimation is still rough, while after 12-15 is stable as the 12-15 and 15-19 group did not differ. Imageability predicted arousal, AoA, emotion- and motor-relatedness indicating that this index influences the way verbs are processed. Imageability was positively correlated to emotion relatedness, indicating that such verbs were harder to be imagined, and negatively to motor relatedness. Imageablity positively correlated with valence meaning that verbs receiving positive valence were also those that were hard to be imagined, and negatively correlated with arousal, meaning that verbs that were harder to be imagined elicited low physiological activation. Our results give an insight in the development of emotional and motor-related verbs representations.